2021
DOI: 10.1111/ajt.16134
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of hepatitis C virus and heterologous immunity on alloimmune responses following liver transplantation

Abstract: Virus‐induced heterologous immunity is considered a barrier to transplantation tolerance. Yet, hepatitis C (HCV)‐infected liver transplant (LT) patients occasionally achieve operational tolerance. We investigated the mechanisms through which HCV infection modulates donor‐specific T cell responses following LT and the influence of HCV eradication. We generated T cell lines from HCV‐infected LT and non‐LT patients before and after HCV eradication and quantified alloreactive responses using cell lines expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…69,70 These changes may persist even after recovery from HCV infection, 69,71 and HCV-induced immune dysfunction can hinder development of heterologous immunity to other antigens, thereby promoting immune frailty. 72 With FDA approval of DAAs for treatment of HCV in 2014, the incidence of transplant for viral positive HCV has declined over time. 73 In creation of the LIFI, we initially evaluated both positive HCV viral load and HCV IgG as potential covariates in multivariate analysis (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…69,70 These changes may persist even after recovery from HCV infection, 69,71 and HCV-induced immune dysfunction can hinder development of heterologous immunity to other antigens, thereby promoting immune frailty. 72 With FDA approval of DAAs for treatment of HCV in 2014, the incidence of transplant for viral positive HCV has declined over time. 73 In creation of the LIFI, we initially evaluated both positive HCV viral load and HCV IgG as potential covariates in multivariate analysis (not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Review chronic rejection has been reported when DAA therapy is delayed, 76,77 highlighting the importance of monitoring for immunemediated events in the context of DAA therapy. 79,80…”
Section: S186mentioning
confidence: 99%
“…However, it has also been suggested that incidence of certain γδ T-cells is driven by systemic viral infections [112,113]. Recently, in vitro experiments have described a role for virus-specific cells in suppression of alloresponses, which provides a possible explanation for the prevalence of γδ T-cells in operationally tolerant as well as hepatitis C virus-positive LT recipients [114]. The functional significance of DCs and γδ T-cells in the development of tolerance requires further investigation.…”
Section: Biomarkers Of Immune Tolerance In Liver Transplantationmentioning
confidence: 99%